Students’ Errors in Using the Simple Present Tense at Polytechnic ATI Padang - Indriani, Silvia (Lingua Cultura, 2019)
The research aimed at analyzing the errors in using simple present tense at Logistics Management of Agro-Industry of Polytechnic ATI Padang. A qualitative method with descriptive approach was applied. The samples were 15% of 153 total students or 23 students. Data were collected through the writing test; namely, descriptive essay. The results show that many students commit errors in using the simple present tense. The errors are classified into four types: omission, addition, misinformation, and misordering. There are 107 errors with the highest number that is omission (61 errors or 57%). Misinformation is in second place with 29 errors (27,1%). The error of addition gains 11,2 % with 12 errors. The lowest error is misordering, which gains 4,7% with only five errors. In conclusion, the most dominant error made by the students is omission with 57% and misordering is the lowest one with 4,7%. Therefore, the lecturers are expected to improve the teaching strategies in teaching simple present tense to reduce the numbers of students’ errors.